A systematic approach towards the integration of initial airworthiness regulatory requirements in remotely piloted aircraft system conceptual design methodologies - Gómez-Rodríguez, Álvaro; Turkoglu, Cengiz; Cuerno-Rejado, Cristina (MDPI, 2024)
The regulatory framework of Remotely Piloted Aircraft Systems (RPASs) has recently experienced an extraordinary evolution. This article seeks to improve the integration of certification considerations in RPAS conceptual design approaches so as to enhance the safety, certifiability and competitiveness of their resulting designs. The first part of the research conducts a two-stage analysis of contemporary regulations related to an RPAS’s initial airworthiness. In the first stage, the broad international regulation paradigm is evaluated attending to a set of criteria that are tightly related to both airworthiness and design considerations. The second stage keeps the most promising documents from a design–integration standpoint, which are assessed according to their applicability considering both design and operational aspects. The results of this analysis provide insights regarding the main issues in airworthiness design criteria extraction and integration in design methodologies. To aid the designer in surmounting these challenges, a flexible procedure named DECEX is developed. Considering the documents and findings from the survey, and attending to the scope of the design methodology being developed, it aids in establishing a complete regulatory document corpus and in comparing and extracting the applicable airworthiness design criteria. Two case studies for different RPAS types are conducted to demonstrate its application.
Keywords: 40 Engineering; 4001 Aerospace Engineering; remotely piloted aircraft systems (RPASs); initial airworthiness regulations; RPAS regulations; RPAS airworthiness; regulation analysis; RPAS conceptual design; design–airworthiness integration; design criteria extraction